Письмо, найденное в Ольвии в 2010 году - Митина, В. В. (Hyperboreus, 2018)
The article is devoted to the analysis of a letter on a lead tablet published for the ﬁrst time by V. I. Nazarchuk (2011). The letter was found in 2010 in Olbia during the investigation of an upper rubble layer formed in the ﬁrst centuries AD over a settlement dated to the Hellenistic period. Because of a lack of reliable archeological context for the site, the letter was dated on the basis of paleographic features. This article contains a table that includes paleographic data regarding the Olbian and Berezan letters and grafﬁti currently known. On the basis of an analysis of the script of these inscriptions, the letter can be dated to approximately the middle of the 5th century BC. Since the tablet is in poor condition and the length of the lines cannot be determined even approximately, it is only possible to restore isolated words in gaps. The tentative restoration of the text in the Ionic dialect: [- - - χλ]ανίδ[α ? - - - - -]χρήμα[τα- - -] /ΥΣΩΙ(?) τούτωι [- - -]καὶ το[- - -] / αι τῆς μητρὸς θή[κ]ην πεν[τε- - -] /ἕκτας ἰδὲ μὴ ταῦτα ποιήσ[ηις e.g. - - -] ΕΣΣΙ τὸν οἶκον ξυν[- - - ]/τα. – “[—]coat (?)money (goods)? [—] / [—]him[—] and [—] / mother’s coffer(?) [—]ﬁve ? [—] /hectes. Beware of doing it (Look! Do not do it). [—]/[—]house [—]/[—]”. Like the majority of private letters found in the northern Black Sea area, the letter treats matters of household economy. Especially noteworthy is the mention in the 4th line of the letter of monetary units (ἕκτας), viz. fractions of Cyzicines, which were widespread in the Greek colonies on the northern shore of the Black Sea. Cyzicines also served in the domestic market in Olbia, at an earlier stage of its history, as coins of large nominal value. The letter thus conﬁrms the circulation of Cyzicene staters in Olbia in the 5th BC, corresponding to the archaeological data.